2023
DOI: 10.3390/molecules28073066
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physicochemical and Bioactive Properties of Quince (Cydonia oblonga Mill.) and Its Products

Abstract: Quince (Cydonia oblonga Miller) is a plant that is commonly cultivated around the world, known for centuries for its valuable nutritional and healing properties. Although quince fruit are extremely aromatic, due to their high hardness and sour, astringent, and bitter taste, they are not suitable for direct consumption in an unprocessed form. However, they are an important raw material in fruit processing, e.g., in the production of jams, jellies, and juices. Quince fruits fall under the category of temperate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 97 publications
0
5
1
Order By: Relevance
“…Quince juice had the lowest titratable acidity, which is confirmed in the literature. However, the obtained titratable acidity value converted to citric acid was lower than the literature data, with it ranging from 3.8 to 7.6 g/L [36][37][38]. This may be because, in published works, fresh quince juice is most often tested, and the juice used in our research is commercially available.…”
Section: Acidity Of the Analyzed Juices And Tea Infusionscontrasting
confidence: 60%
“…Quince juice had the lowest titratable acidity, which is confirmed in the literature. However, the obtained titratable acidity value converted to citric acid was lower than the literature data, with it ranging from 3.8 to 7.6 g/L [36][37][38]. This may be because, in published works, fresh quince juice is most often tested, and the juice used in our research is commercially available.…”
Section: Acidity Of the Analyzed Juices And Tea Infusionscontrasting
confidence: 60%
“…Legua et al [82] showed that the total concentration of carotenoids was higher in the peel (0.16-0.86 mg/100 g, depending on the clone) than in the pulp (0.04-0.42 mg/100 g) and that the color of the peel did not correlate with the color of the pulp. In recent studies by Najman et al [83,84], the authors compared the total trans carotenoid content in fresh, dried, and processed fruits and obtained higher values. The β-carotene content was 13.6 mg/100 g fm, and the xanthophyll levels were significantly lower: 3.5 and 1.4 mg/100 g fm for lutein and zeaxanthin, respectively.…”
Section: Ascorbic Acid Carotenoids and Other Antioxidantsmentioning
confidence: 99%
“…Legua et al [86] showed that the total concentration of carotenoids was higher in the peel (0.16-0.86 mg/100 g, depending on the clone) than in the pulp (0.04-0.42 mg/100 g) and that the color of the peel did not correlate with the color of the pulp. In recent studies by Najman et al [87,88], the authors compared the total trans carotenoid content in fresh, dried and processed fruits and obtained higher values. Among the carotenoids, the β-carotene content was 13.6 mg/100 g fm, and the xanthophylls content was significantly lower: 3.5 and 1.4 mg/100 g fm, for lutein and zeaxanthin, respectively.…”
Section: Phenolic Compoundsmentioning
confidence: 99%